Workshop Pengembangan Alur Tujuan Pembelajaran dan Modul Ajar Berbantuan Aplikasi Penilaian - Rini, Rini Triastuti; Wijianto, Wijianto; Raharjo, Raharjo; Nuryadi, Muhammad Hendri (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
The problems faced by partners are in the form of teacher Civic teachers in Pacitan Regency had difficulties in preparing individual learning tools. Therefore, the Citizenship Learning and Education Research Group conducted a workshop on developing Learning Objective Flows and Teaching Modules with the help of Assessment Applications. The purpose of the service is to improve the teacher's ability to develop learning designs. The service method used is in the form of a workshop with a blended learning model. Implementation is carried out in five stages, namely identifying the characteristics of workshop participants, preparing materials, creating digital classes and the necessary platforms, carrying out offline and online workshops, evaluating workshop results. The result of the service is that after attending the workshop, the teacher can make ATP and modules according to the criteria. while additional outputs are in the form of publications in online media and community service videos.